Recombinant Heparin—New Opportunities - Glass, Charles Alexander (Frontiers in Medicine, 2018)
Heparin and heparan sulfate (HS) are polydisperse mixtures of polysaccharide chains between 5 and 50 kDa. Sulfate modifications to discreet regions along the chains form protein binding sites involved in cell signaling cascades and other important cellular physiological and pathophysiological functions. Specific protein affinities of the chains vary among different tissues and are determined by the arrangements of sulfated residues in discreet regions along the chains which in turn appear to be determined by the expression levels of particular enzymes in the biosynthetic pathway. Although not all the rules governing synthesis and modification are known, analytical procedures have been developed to determine composition, and all of the biosynthetic enzymes have been identified and cloned. Thus, through cell engineering, it is now possible to direct cellular synthesis of heparin and HS to particular compositions and therefore particular functional characteristics. For example, directing heparin producing cells to reduce the level of a particular type of polysaccharide modification may reduce the risk of heparin induced thrombocytopenia without reducing the potency of anticoagulation. Similarly, HS has been linked to several biological areas including wound healing, cancer and lipid metabolism among others. Presumably, these roles involve specific HS compositions that could be produced by engineering cells. Providing HS reagents with a range of identified compositions should help accelerate this research and lead to new clinical applications for specific HS compositions. Here we report progress in engineering CHO cells to produce heparin and HS with compositions directed to improved properties and advancing medical research.